The inherence of human dignity : subtitle law and religious liberty. Volume 2 - Bussey, Barry W., 1965-; Menuge, Angus J. L. (London : Anthem Press, 2021)
For the 2019 IVR World Congress of Philosophy of Law meeting in Lucerne, Switzerland, Drs Barry W. Bussey and Angus J. L. Menuge organized a special workshop on the inherence of human dignity, featuring participation from philosophers, legal scholars, and legal practitioners from around the world. Many of the chapters in these volumes are the result of that invigorating two-day workshop. In addition, several new papers were solicited to round out each volume so that it offers broad coverage of the issues it addresses. The first volume, Foundations of Human Dignity, focuses on the foundational questions concerning the meaning, nature, and scope of human dignity, and our ability to know it. It addresses the following questions: It addresses the following questions. How was dignity understood by the drafters of the Universal Declaration of Human Rights? Can human dignity be grounded in natural characteristics of human beings accessible by reason, or must it be grounded in God? How can we recognize and promote dignity? What is the connection between dignity and religious liberty? Should dignity be understood in terms of autonomy or well-being? What is the origin of the new dignity jurisprudence, and is it defensible? Can dignity be understood as social characteristic? Can it be extended to artificially intelligent systems?
Title from publisher's bibliographic system (viewed on 24 Feb 2022).
Keywords: Respect for persons -- Law and legislation; Dignity -- Religious aspects; Dignity